Abrasive wear behavior of Al-TiB2 and Al-TiB2-nano-graphite metal matrix composites. (May 2021) - Poria, Suswagata; Sutradhar, Goutam; Sahoo, Prasanta
This paper deals with abrasive wear behavior of two different composite materials namely Al-TiB2 and Al-TiB2 -nano-graphite. At the time of fabrication, ultrasonic vibration is used along with mechanical stirrer to obtain uniform dispersion of micro (TiB2 ) and nano (graphite) reinforcement phase. Uniform dispersion is confirmed through SEM images of cast composites. Micro-hardness values are obtained for composites and base alloy. Wear tests under two-body abrasion are performed by a tribological test apparatus where composite pins are being rubbed against a disc holding different grades of SiC abrasives: 240 grit, 320 grit and 400 grit. Operating load is varied between 10N and 30N while sliding speed and duration of sliding are kept fixed. Effects of load, reinforcing phase content and abrasive grit size on abrasive wear and friction behavior have been evaluated. Al-TiB2 composites demonstrate higher wear resistance and better friction behavior in comparison with base alloy under all operating conditions. Addition of nano-graphite phase contributes in achieving better abrasive wear and friction performance of Al-TiB2 composites. With increase in grit size, wear reduces for composites and base alloy while wear increases with load. Worn surfaces of samples and emery papers are studied using SEM micrographs and EDX maps. Wear debris at different operating conditions are studied also using SEM and EDX. Operative wear mechanisms are identified from the experimental results.